Intravitreal Steroid Treatment for Uveitis Associated with Dabrafenib and Trametinib for Metastatic Cutaneous Melanoma. (4th July 2021) - Woltsche, Nora; Kruger, Michael Andreas; Weger, Martin; Wolf, Ingrid Hildegard; Seidel, Gerald
ABSTRACT: Purpose : To report a case of bilateral retinal inflammation under long-term therapy with dabrafenib/trametinib for metastatic cutaneous melanoma. Methods : Retrospective chart review. Results : A 59-year-old patient with metastatic cutaneous melanoma diagnosed in 2004 under treatment with dabrafenib/trametinib since 2014 presented to our department with intraretinal hemorrhage and extrafoveal macula edema on the right eye and optic disc swelling on the left eye. The patient did not report visual complaints. After cessation of dabrafenib/trametinib and subconjunctival and intravitreal corticosteroid injections, optic disc swelling on the left eye recovered after 6 months. The macula edema on the right eye was treated with one intravitreal anti-VEGF (vascular endothelial growth factor) injection after encroaching upon the fovea 10 months after initial presentation. The final visual acuity was 20/20 on both eyes. Conclusion : Even after years of treatment with low dose dabrafenib/trametinib, ocular toxicity can develop. Such cases can respond well to intravitreal corticosteroids.